A new semi-active control strategy on lateral suspension systems of high-speed trains and its application in HIL test rig. Issue 5 (4th May 2023) - Yang, Shaopu; Zhao, Yiwei; Liu, Yongqiang; Liao, Yingying; Wang, Peng
Abstract : With the increasing speed of trains, the lateral vibration of the car body becomes violent and the ride comfort becomes worse. This study adopts semi-active control techniques to reduce the excessive vibration of the car body. A novel control strategy and its extended control strategy, Displacement-Velocity (DV) and Sky-hook (SH)-DV, are presented and applied to the magnetorheological (MR) dampers. The semi-active suspension system of MR dampers is integrated into a quarter model and a 17 degrees of freedom (DOF) train model instead of the passive suspension, respectively. The theoretical simulations are performed and compared with the SH control strategy. Furthermore, the hardware in the loop (HIL) test based on MR dampers is built and experimental research is carried out. In the theoretical simulations and experimental research, multiple service conditions are adopted, and the dynamic performance of highspeed trains is evaluated. Theoretical and experimental results indicate that the new control strategies can significantly suppress the vibration of the car body, and they can ensure the safety and stability of the high-speed train. Moreover, their control and robust performance (about time delay) are better than that of the SH, especially the DV. Therefore, this paper provides an additional choice for the methods of vibration control.